The resource value of indigenous plants to rural people in a low agricultural potential area (Volume 1) - Balfour-Cunningham, Anthony (Department of Biological Sciences, 2018)
This is essentially an ethno-botanical study that explores the borderland between nature conservation, plant use and people. The study area situated at the southern end of the large coastal plain stretching down the east coast of Africa from Somalia to Natal, South Africa. Roughly rectangular in shape, and 1900 km² in extent, it farms a major part of an area known as Maputaland or Tongaland in Natal/KwaZulu. Since this study was initiated, Bruton and Cooper (1980) and Tinley and van Riet ( 1981) have synthesised the available information on Maputaland. This provides an excellent background to the climate, and development of the geology, natural resources, history study area. Mapping of amenities, soils, vegetation, geology, agricultural development and potential has been done on a 1:100 000 scale by Loxton et al, 1969. These data were used as a basis for smaller scale maps by Tinley and van Riet (1981) who also provided detailed descriptive information on climate, soils and ecology of the area. Because of these previous studies, and the fact that the book by Bruton and Cooper (1980) is readily available, descriptive detail has been kept to a minimum.